Body checking and its avoidance in eating disorders. - Shafran, R; Fairburn, C; Robinson, P; Lask, B (2004)
OBJECTIVE: One expression of the core psychopathology of eating disorders is the repeated checking and avoidance of shape or weight. Two studies are reported. The primary purpose of the first was to describe the phenomenology of such body checking and avoidance. The aim of the second was to compare body checking and avoidance in women with and without a clinical eating disorder. METHOD: In Study 1, 64 female patients with clinical eating disorders participated in a semistructured interview assessing the features of body checking and avoidance. In the second study, a self-report questionnaire was used to compare body checking and avoidance in women with and without a clinical eating disorder (n = 110). RESULTS: The majority (92%) of the patients in Study 1 checked their bodies to assess their shape or weight and this was associated significantly with eating disorder symptoms. In Study 2, the clinical group had significantly more body checking and avoidance than the comparison group, and there was a strong association between eating disorder psychopathology and body checking and avoidance. CONCLUSIONS: These findings support the view that body checking and avoidance are direct expressions of the overevaluation of shape and weight. Further work is needed to determine whether these expressions contribute to the maintenance of eating disorders.